2019
DOI: 10.1002/gps.5174
|View full text |Cite
|
Sign up to set email alerts
|

Are loneliness and social isolation associated with cognitive decline?

Abstract: Objective This study aimed to examine the association of loneliness and social isolation on cognition over a 3‐year follow‐up period in middle‐ and older‐aged adults. Methods Data from a Spanish nationally representative sample were analyzed (n = 1691; aged 50 years or older). Loneliness, social isolation, and cognition (immediate recall, delayed recall, verbal fluency, forward digit span, backward digit span, and a composite cognitive score) were assessed both at baseline and at follow‐up. Adjusted generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
189
2
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(213 citation statements)
references
References 62 publications
9
189
2
13
Order By: Relevance
“…Long periods of social isolation may have a profound negative effect on mental health conditions including depression, anxiety, stress and insomnia ( 8 ), may differ as a function of sex and age ( 5 ), and may worsen health inequalities, with poorer and marginalized groups at greatest risk ( 9 ). Furthermore, social isolation, loneliness and depression have, in turn, been associated with cognitive decline ( 10 , 11 ) and incident dementia ( 12 , 13 ) among older people.…”
Section: Introductionmentioning
confidence: 99%
“…Long periods of social isolation may have a profound negative effect on mental health conditions including depression, anxiety, stress and insomnia ( 8 ), may differ as a function of sex and age ( 5 ), and may worsen health inequalities, with poorer and marginalized groups at greatest risk ( 9 ). Furthermore, social isolation, loneliness and depression have, in turn, been associated with cognitive decline ( 10 , 11 ) and incident dementia ( 12 , 13 ) among older people.…”
Section: Introductionmentioning
confidence: 99%
“…The mental well-being of people with dementia who are socially isolating is also considered to be at extremely high risk and a thorough clinical management of this population is regarded as a top priority, especially for those living in care homes, since up to 98% of them present with neuropsychiatric symptoms (6,7). In fact, a significant association between social isolation and both mental health (8) and levels of cognitive abilities (9) has already been observed in older adults and appears to be mediated by loneliness, i.e., the subjective perception of social isolation. Moreover, greater loneliness has also been found to be significantly associated with reduced brain volume in areas in the left medial temporal lobe involved in memory and harshly affected by AD (10).…”
Section: Introductionmentioning
confidence: 99%
“…4 An association between social isolation and cognitive functioning has been demonstrated by recent cross-sectional 5 and longitudinal studies. 6,7 For example, it has been shown that social isolation is related to decreased cognitive function based on data from a A recent systematic review on the longitudinal association between social isolation and cognitive functioning showed that these factors are weakly associated. 8 However, most of these longitudinal studies focused on social network and social activities without using standardized instruments (eg, using living alone as a surrogate for social isolation).…”
Section: Introductionmentioning
confidence: 99%